C형 및 S형 단백 결핍에 의한 혈관 질환 - 조용필(Yong Pil Cho); 이덕희(Deok Hee Lee); 정승문(Seung Mun Jung); 장혁재(Hyuk Jai Jang); 김지수(Jee Soo Kim); 한명식(Myoung Sik Han) (Annals of surgical treatment and research, 2002)
Purpose: There are a number of conditions that can lead to a hypercoagulable state, however, protein C and S deficiencies are frequently described as causes of the hypercoagulable states. The aim of this study was to evaluate the clinical features and prognosis of vascular diseases associated with protein C and/or S deficiencies and to determine an adequate treatment modality for such cases. Methods: We prospectively evaluated 7 cases with vascular disease caused by protein C and/or S deficiencies confirmed with serologic tests. Results: Four patients showed venous thrombosis, 1 peripheral arterial insufficiency, 1 cerebral venous thrombosis and peripheral arterial insufficiency, and 1 portal vein thrombosis. Surgical intervention was required in 5 patients. Full anticoagulation with heparin sodium followed by warfarin sodium was done in all patients. Conclusion: Protein C and S deficiencies may influence clinical management. Patients presenting with atypical vascular involvement without evidence of other risk factors should be evaluated for a hypercoagulable state. Once the diagnosis is made, patients should be treated with full anticoagulation. (J Korean Surg Soc 2002;62:181-186) KCI Citation Count: 2